STRATEGIES FOR CONSECUTIVE INTERPRETING IN JOKO WIDODO'S ASEAN BUSINESS AND INVESTMENT FORUM SPEECH - Okta Viana Dwi Lestari; Ramadan Adianto Budiman (Acceleration: Multidisciplinary Research Journal, 2024)
This study explores the consecutive interpreting strategies used in President Joko Widodo's speech at the ASEAN Business and Investment Forum, focusing on how these strategies contribute to enhancing the effectiveness of cross-cultural diplomatic communication. This research provides valuable insights into professional interpreting practices and contributes significantly to the development of interpreting studies, particularly in the field of diplomacy and international communication. The main focus of the research is on three strategies: modulation, transposition, and amplification. Using a descriptive qualitative approach and data from YouTube, this study identifies and analyzes the interpreter strategies applied in the interpretation of messages from Indonesian to English. The results show that successful consecutive interpreting depends not only on linguistic ability but also on a deep understanding of the cultural and political context, as well as the ability to manage diplomatic nuances. This research provides valuable insights into professional interpreting practices at high governmental levels and is expected to contribute significantly to the field of interpreting studies, especially in the context of diplomacy and international communication.